IDENTIFICATION OF ISLET CAPACITY IN DONOR’S PANCREAS USING IMMUNOMORPHOLOGICAL ANALYSIS - N. N. Skaletskiy; L. A. Kirsanova; G. N. Bubentsova; N. V. Baranova; G. N. Skaletskaya; V. I. Sevastianov (Вестник трансплантологии и искусственных органов, 2016)
The aim of the work was detailed morphological investigations of donor pancreas (DP) for the study of possibilities of maximal selection of islet tissue suitable for transplantation to a patient of diabetes mellitus type 1.Materials and methods. Eight DPs were received as a result of multiorgan donation. Morphological investigations were performed by means of histological and special immunohistochemical methods.Results. The Majority of islets were revealed in the tail part of the DP. Besides typical Langerhans islets with predominance of mosaically located beta cells, the accumulations of islet cells forming so-called interlobular (perilobular) islets were revealed in the layers of interlobular connecting tissue. In addition, in the cells of ductal epithelium nestin which is a marker of progenitor cells was revealed.Conclusion. To obtain the maximal potential of islet tissue from DP it is necessary to use interlobular located islets as well as to use progenitor cells of pancreas, which have the ability to transdifferentiate into islet cells.